A high-throughput platform for population reformatting and mammalian expression of phage display libraries to enable functional screening as full-length IgG. Issue 6 (18th August 2017) - Xiao, Xiaodong; Douthwaite, Julie A.; Chen, Yan; Kemp, Ben; Kidd, Sara; Percival-Alwyn, Jennifer; Smith, Alison; Goode, Kate; Swerdlow, Bonnie; Lowe, David; Wu, Herren; Dall'Acqua, William F.; et al.
ABSTRACT: Phage display antibody libraries are a rich resource for discovery of potential therapeutic antibodies. Single-chain variable fragment (scFv) libraries are the most common format due to the efficient display of scFv by phage particles and the ease by which soluble scFv antibodies can be expressed for high-throughput screening. Typically, a cascade of screening and triaging activities are performed, beginning with the assessment of large numbers of E. coli -expressed scFv, and progressing through additional assays with individual reformatting of the most promising scFv to full-length IgG. However, use of high-throughput screening of scFv for the discovery of full-length IgG is not ideal because of the differences between these molecules. Furthermore, the reformatting step represents a bottle neck in the process because each antibody has to be handled individually to preserve the unique VH and VL pairing. These problems could be resolved if populations of scFv could be reformatted to full-length IgG before screening without disrupting the variable region pairing. Here, we describe a novel strategy that allows the reformatting of diverse populations of scFv from phage selections to full-length IgG in a batch format. The reformatting process maintains the diversity and variable region pairing with high fidelity, and the resulted IgG pool enables high-throughput expression of IgG in mammalian cells and cell-based functional screening. The improved process led to the discovery of potent candidates that are comparable or better than those obtained by traditional methods. This strategy should also be readily applicable to Fab-based phage libraries. Our approach, S creeningi nP roductF ormat (SiPF), represents a substantial improvement in the field of antibody discovery using phage display.